The Relationship Between Unexplained Chest Pain in Children and Head-Up Tilt Test - Wang, Ying; Wang, Shuo; Zou, Runmei; Chen, Siyang; Li, Fang; Wang, Yuwen; Xu, Yi; Wang, Cheng (Frontiers in Pediatrics, 2022)
Background To explore the relationship between unexplained chest pain in children and head-up tilt test (HUTT). Materials and Methods A total of 825 children with the main symptom of unexplained chest pain were admitted to the Specialist Outpatient Clinic of Children’s Cardiovascular Disease from October 2000 to November 2021 at The Second Xiangya Hospital, Central South University. Among them, 473 were male and 352 were female, with a mean age of 10.61 ± 2.21 years. The control group included 58 cases, comprising 35 males and 23 females, with a mean age of 10.26 ± 2.66 years. The detailed history, physical examinations, conventional 12-lead electrocardiogram, chest X-ray, echocardiography, myocardial enzymes, electroencephalogram, and blood series were all examined. Disorders of the chest wall, lung, heart, mediastinum, and esophageal reflux, as well as drug effects, were ruled out. All the children underwent HUTT. Demographic description, univariate analysis, and multivariate logistic regression analysis were used to explore the possible linear or non-linear relationships between the children’s unexplained chest pain and HUTT. Results Among the 825 chest pain cases, 301 (36.48%) were HUTT positive and 524 (63.52%) were HUTT negative. HUTT-positive patients were older than HUTT-negative patients (11.04 ± 2.03 vs. 10.34 ± 2.31 years, P < 0.001). The logistic regression results showed that each year of age increased the probability of being HUTT positive by 17.90% (P < 0.000), and females were 91.30% more likely to be HUTT positive than males (P < 0.000). Conclusion Clinically unexplained chest pain in children is mainly caused by unbalanced autonomic nervous function. HUTT can help clear the cause of unexplained chest pain.